2012
DOI: 10.1136/gutjnl-2012-303594
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant p53 protein expression is associated with an increased risk of neoplastic progression in patients with Barrett's oesophagus

Abstract: Aberrant p53 protein expression is associated with an increased risk of neoplastic progression in patients with BO and appears to be a more powerful predictor of neoplastic progression than histological diagnosis of LGD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
179
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 221 publications
(193 citation statements)
references
References 38 publications
12
179
1
1
Order By: Relevance
“…Recent promising work in a case-control study suggested that aberrant p53 expression defi ned as absent or increased expression by immunohistochemistry was associated with an increased risk of neoplastic progression ( 134 ). However, it appears that no single biomarker is adequate as a risk stratifi cation tool.…”
Section: Advanced Endoscopic Imaging Techniquesmentioning
confidence: 99%
“…Recent promising work in a case-control study suggested that aberrant p53 expression defi ned as absent or increased expression by immunohistochemistry was associated with an increased risk of neoplastic progression ( 134 ). However, it appears that no single biomarker is adequate as a risk stratifi cation tool.…”
Section: Advanced Endoscopic Imaging Techniquesmentioning
confidence: 99%
“…It is, however, the overexpression of p53 in LGD that is associated with an increased risk of progression to HGD/EAC [24][25][26] . The concomitant diagnosis of aberrant p53 increased the positive predictive value of neoplastic progression from 15% to 33% [27] . Further the presence of 17p loss of heterozygosity (LOH), which is thought to represent inactivation of p53 has been demonstrated to be a strong predictor of progression in BE [28] .…”
Section: Esophageal Adenocarcinomamentioning
confidence: 96%
“…Extensive evidence shows that p53 overexpression is seen in both cancerous and high grade dysplasia and is, thus, predictive of progression [16]. This could be an excellent predictive tool when its overexpression is detected by immunohistochemistry [17]. Due to the complexity of the control of the cell cycle and the amount of genetic alterations that can occur, it is likely that mutations will vary between patients and there may not be a single trigger that will be able to explain, nor predict, progression, but rather an accumulation of changes that will ultimately push the cell towards carcinoma.…”
Section: Dysplasiamentioning
confidence: 99%